Matrix Metalloproteinases-3, -9, and Prolidase: A Promising Therapeutic Strategy Targeting Breast Cancer: MMP-3, MMP-9 & Prolidase in Breast Cancer - Jabbar , Samar Ahmed; Fadhil, Ola H.; Mahmood, Noah Abdalkader; Shallal Murad Hussein (Iraqi Journal of Cancer and Medical Genetics, 2025)
Matrix metalloproteinases (MMPs) are tightly regulated enzymes that play a significant role in tissue remodeling. They are produced by normal and tumor cells and participate in extracellular matrix remodeling and degradation of basement membrane barriers. During tumor progression, cancer cells invade surrounding tissues, accompanied by numerous alterations, leading to microenvironmental stress and breakdown of the extracellular matrix, including loss of basement membrane integrity caused by dysfunction of metalloproteinase activity. This review summarizes the significant roles of MMP-3, -9, and prolidase in different stages of breast cancer progression to offer a comprehensive understanding of the main contributions of these enzymes in breast tumors. Studies have indicated that elevated expression and enzymatic activity correlate with tumor progression through the modulation of transcription factor activity and metastasis mechanisms. MMP-3 is involved in angiogenesis; inhibition of MMP-3 activity is considered a potential therapeutic strategy. In contrast, MMP-9 plays a restrictive role in angiogenesis. Numerous studies have shown that targeting tissue inhibitors of MMPs or silencing these enzymes represents a promising therapeutic strategy to suppress tumor growth and enhance apoptosis. MMP-3, MMP-9, and prolidase should not be considered independent regulators of extracellular matrix remodeling; they function through interconnected mechanisms that govern the dynamic remodeling of cancer progression. Few studies have investigated prolidase activity and its role in pathological processes, and its precise association with MMP-3 and MMP-9 in breast cancer remains poorly understood. Currently, no studies have directly discussed the relationship between MMP-3 and prolidase; however, few mechanistic studies have indicated that prolidase acts as an upstream regulator of MMP-3 and MMP-9 in breast cancer. Further experimental investigations are needed to clarify the interplay of these enzymes in extracellular matrix remodeling within the breast tumor microenvironment to support the development of a prospective therapeutic approach.